Organizadores gráficos y su contribución al proceso de enseñanza- aprendizaje en la asignatura de Estudios Sociales, en los alumnos de décimo año paralelo A, de la Unidad Educativa Fiscomisional Monseñor Alberto Zambrano Palacios, cantón Olmedo, periodo 2018-2019. Lineamientos alternativos - Cordova Jimenez, Sonia Elizabeth (2019)
The research Graphic organizers and their contribution to the teaching-learning process in the subject of Social Studies, in the students of the tenth parallel year A, of the Educational Division of the Monseñor Alberto Zambrano Palacios, Canton Olmedo, period 2018-2019. Alternative guidelines, aimed to determine the contribution of graphic organizers and their application to facilitate the teaching-learning process in the subject of Social Studies. It was sustained in the descriptive study; methods: descriptive, analytical, synthetic, observational and statistical; techniques: observation, survey and interview; instruments: observation guide, questionnaire and interview guide; and, the procedures: theoretical foundation, diagnosis and design of the alternative guideline taking as reference the diagnosis made to the teaching-learning process of Social Studies, where the main problem detected is the lack of use of techniques as a learning mechanism that are of interest of students, including graphic organizers. The participating sample was 23 students and 1 teacher. The work is concluded confirming the importance of the graphic organizers and their contribution to the learning of the subject of Social Studies.